A mapping analytic approach to trace development of multidisciplinary research field: The case on e-health in China. Issue 2 (6th July 2015) - Zhang, Xi; Yan, Xiangda; Ordóñez de Pablos, Patricia; She, jinghuai; Gao, Yang; Chen, Hui
Abstract : Purpose: – This paper aims to provide clear domain knowledge and recent progresses on electronic healthcare (e-healthcare). Design/methodology/approach: – In this paper, the authors use citation analysis to describe the trends of study on e-health with the help of CiteSpace II, a software for visualizing citation-based analysis. By analyzing the 2, 752 publications and their citation data in ISI database, the authors proposed renewable figures and tables on ranking critical people, institutes, keywords and journals. Through the most influential articles given by CiteSpace, the authors can grasp the main direction in e-health researches. Furthermore, the authors analyzed the literature at e-health literacy as a case, to better understand the development of research viewpoints. Findings: – Through the analysis, the authors found that e-health is a multi-disciplinary research field and the major research about it has changed. During the early stage, health information quality on the Internet dominates. Gradually, the role of information technology (IT) becomes more important. The authors also found that some researchers, recently, have proposed the effects of IT on e-health literacy which can then improve the ability to use health information on the Internet. Research limitations/implications: – This paper has some research limitations, such as using an ISI database with most English publications. The future research may be conducted for collecting local publications data in China. It also has some implications. Based on the results, the authors claimed that IT may significantly improve people's healthcare variance, e.g. e-health literacy. It is necessary to build new IT-based healthcare theories. Practical implications: – This paper also has some practical implications. Practitioners and institute may easily come to know which are the hot topics, top institutes and tendencies in the e-healthcare field. Social implications: – This paper may help practitioners to find common interests with other institutions and societies. Originality/value: – This paper reported the status and trend of research in this field visually, and the result will help researchers to do more in-depth research in the future.